2007
DOI: 10.1177/0009922807300420
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in the Management of Common Painful Conditions of Preschool Children in United States Pediatric Emergency Departments

Abstract: Trends in pain management practice by Pediatric Emergency Medicine fellows in the United States were described and analyzed. Self-administered surveys on pain management practices conducted among Pediatric Emergency Medicine fellows at the national Pediatric Emergency Medicine fellows' annual conference in 1996 and 2004 were compared. In comparison to the 1996 survey, the 2004 survey noted a significant increase in narcotics use for headache (6% versus 12%; P = .001), abdominal pain (4% versus 50%; P = .001), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…66 Results showed that intranasal ketamine was not superior to IV metoclopramide; however, the study suggests that intranasal ketamine may have pain-reliving effects comparable to IV migraine abortive therapies. A review of treatment trends in the ED found an increase in ketamine use in pediatric patients presenting with lacerations and skeletal fractures; 67 however, there is a lack of studies evaluating the use of ketamine specifically for acute migraine treatment in the pediatric population. One longitudinal cohort study of 63 pediatric patients treated at a tertiary care center for various chronic pain conditions, including migraine (13%), reported that "ketamine-associated reductions in pain scores were the largest in postural orthostatic tachycardia syndrome and trauma patients and the smallest in patients with chronic headache."…”
Section: Expert Opinionmentioning
confidence: 99%
“…66 Results showed that intranasal ketamine was not superior to IV metoclopramide; however, the study suggests that intranasal ketamine may have pain-reliving effects comparable to IV migraine abortive therapies. A review of treatment trends in the ED found an increase in ketamine use in pediatric patients presenting with lacerations and skeletal fractures; 67 however, there is a lack of studies evaluating the use of ketamine specifically for acute migraine treatment in the pediatric population. One longitudinal cohort study of 63 pediatric patients treated at a tertiary care center for various chronic pain conditions, including migraine (13%), reported that "ketamine-associated reductions in pain scores were the largest in postural orthostatic tachycardia syndrome and trauma patients and the smallest in patients with chronic headache."…”
Section: Expert Opinionmentioning
confidence: 99%